2012
DOI: 10.1016/j.jcrs.2012.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic nepafenac and ketorolac versus placebo in preventing postoperative macular edema after uneventful phacoemulsification

Abstract: One month after uneventful phacoemulsification, there was no difference in macular volume between the placebo, ketorolac, and nepafenac. Ketorolac and nepafenac were well tolerated with minimal side-effect profiles. Thus, for patients without risk factors having routine surgery, prophylactic topical NSAIDs are not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 16 publications
(16 reference statements)
4
36
1
Order By: Relevance
“…However, we observed that higher AH levels of CCL2 were associated with greater degree of CE in diabetic patients, which indicates that CCL2 may prolong postoperative recovery in cataract patients burdened with chronic proinflammatory activity. 38 NSAID pretreatment, mostly applied as a prophylaxis for macular edema, 39,40 was able to lower the CCL2 level in the diabetic group of patients, although the difference was not statistically significant (p = .101), indicating a need for further investigation. In addition, we were able to confirm that diabetic and nondiabetic patients may be distinguished based on the AH levels of VEGF, IL-10, and FasL, which could serve as possible therapeutic targets in the preoperative treatment in order to alleviate postoperative complications in diabetic cataract patients.…”
Section: Discussionmentioning
confidence: 87%
“…However, we observed that higher AH levels of CCL2 were associated with greater degree of CE in diabetic patients, which indicates that CCL2 may prolong postoperative recovery in cataract patients burdened with chronic proinflammatory activity. 38 NSAID pretreatment, mostly applied as a prophylaxis for macular edema, 39,40 was able to lower the CCL2 level in the diabetic group of patients, although the difference was not statistically significant (p = .101), indicating a need for further investigation. In addition, we were able to confirm that diabetic and nondiabetic patients may be distinguished based on the AH levels of VEGF, IL-10, and FasL, which could serve as possible therapeutic targets in the preoperative treatment in order to alleviate postoperative complications in diabetic cataract patients.…”
Section: Discussionmentioning
confidence: 87%
“…In a similar study by Almeida et al 9 evaluating the efficacy of prophylactic NSAIDs versus placebo on macular volume 1 month after phacoemulsification, in patients with no risk factors for macular oedema and no intraoperative complications, the authors found no statistically significant differences between the three study groups (p=0.29). This study concluded that in low-risk patients, prophylactic use of topical ketorolac or nepafenac seems to offer no benefit in preventing OCT changes indicative of macular oedema after surgery.…”
Section: Discussionmentioning
confidence: 88%
“…These findings are worse than those of Donnenfeld et al 13 who report that 3-day and 1-day dosing of ketorolac reduced surgical time, endothelial cell loss and improved visual acuity in the immediate postoperative period compared with placebo. In another study that evaluated the efficacy of prophylactic ketorolac versus nepafenac versus placebo by Almeida et al 9 there was no difference in mean values or ranked mean values of CDVA between the placebo group and the NSAIDs groups after 1 month of follow-up.…”
Section: Discussionmentioning
confidence: 91%
“…1,2 Ketorolac has also been shown to reduce or prevent cystoid macular edema after routine cataract surgery. 3 Brand diclofenac and brand ketorolac were previously shown to have anesthetic effects causing immediate reduction in corneal sensitivity.…”
mentioning
confidence: 99%